THE USING OF 4D FLASHCARD WITH KINESTHETIC STUDENTS TO INCREASE SPEAKING SKILLS - Hardianti Hamzah; Nurhamdah Nurhamdah; Magdahalena Magdahalena (Institut Agama Islam Negeri Parepare, 2019)
The using of technology had developed especially in education. Even though it was had a high technology, some of the teachers did not use it. In this case, this research was introduced a new application media in learning process and it is called Octaland 4D. This application is made by Octagon studio with purposing to give a benefit in education by using 4D flashcards. The research used an experimental design one group pre-test and post-test. The population in this research was the first-year kinesthetic students, in academic year 2017. The samples of this research were the first-year kinesthetic students. The technique of sampling used total sampling, the writer took all population the first-year kinesthetic students to be a sample and the data was analyzed into percentage, mean score analyzed and the value of the t-test. The result of the data analysis showed that the students’ achievement on the post-test was higher that on the pre-test. Moreover, based on the analysis the researcher found that the students speaking skill in English was increased significantly. This research gave a suggestion that using 4D flashcard as the media is a good way in learning process in speaking English.